INTRODUCTION - Mohd Azlan, Jayasilan; Mohamad Kadim, Suaidi; Indraneil, Das (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
The State of Sarawak, with an area of approximately 124,450 km2 , has one of the most established networks of protected areas within Malaysia, representing some of the most megadiverse rainforests of the world. The landscape ranges from coastal lowlands, comprising peat swamps, as well as narrow deltaic and alluvial plains, to a vast hinterland of undulating low hills, that barely reach 300 metres, to the mountainous highlands, that extend to the international border in the interiors of Borneo. The State currently has 67 Totally Protected Areas (including National Parks, Wildlife Sanctuaries and Nature Reserves), scattered throughout the State, a majority located in western Sarawak